Organizations and stratification: Processes, mechanisms, and institutional contexts. (February 2017) - Tomaskovic-Devey, Donald; Avent-Holt, Dustin
Highlights: In this paper we highlight the role of organizations in stratification research historically. We then outline the contributions we see in each paper of the special issue. The papers in this special issues develop relational inequality theory, highlighting organizational variability in mechanisms, processes, and institutional sources of inequality.